Mother's hand tool as a skin-to-skin contact simulation instrument decreases pain levels in newborns - Ceylantekin, Yesim; Duman, Nuriye Buyukkayaci; Ocalan, Dilek; Topuz, Senay; Ucar, Betul Yildiz (Universa Medicina, 2021)
BACKGROUNDSensory stimulation activates the gate control mechanism, raises the level of beta endorphins, and the secretion of beta endorphins increases the pain threshold, reducing or eliminating the feeling of pain. It has been reported that skin-to-skin contact or sensual stimulation reduces stress, pain and crying time in newborns. The present study aimed to examine the effect of the mother’s hand tool (MHT) - developed by the researchers for three purposes: touch, positioning and vibration - on pain levels in newborns. METHODSA quasi-experimental study was conducted involving 52 newborns aged 0-15 days who were being treated in the neonatal intensive care unit. The MHT was applied to support the newborn and was applied 8 times in 24 hours for 3 minutes in total. Demographic data collection form (DDCF), neonatal evaluation form (NEF) to assess the respiratory rate, pulse rate, SPO2 and CO2 level, and neonatal infant pain scale (NIPS) were used to collect data. The Wilcoxon signed rank test was applied to analyse the data. A p value of <0.05 was considered to be statistically significant. RESULTSAfter the MHT application, it was revealed that there was a significant difference in pulse rate (p=0.000), SPO2 level (p=0.029), CO2 level (p=0.000) and NIPS pain scores (hour 6,9,12,15,18, and 24) and total NIPS (p=0.000) pain scores, before and after MHT practice. CONCLUSIONThis study demonstrated that MHT application to the newborns had a decreasing effect on pain level, heart rate, CO2 level, and an increasing effect on SPO2 level.